Pelatihan Instalasi Sound System Area Masjid Di Pesantren Tahfidz Markaz Hadits Bilal Bin Rabah - Sunardi; Angga Septian MN; Jamal A. Rachman Saprin; Candra Mas Bayu; Harisudin Pamungkas (CV. Multi Kreasi Media, 2024)
Markaz Hadits (MH) is a foundation that provides religious education with the core material of memorizing the Koran and the Hadith of the Prophet sallallaahu 'alaihi wasallam, at junior high school (Tsanawiyah) and high school ('Aliyah) levels. Tahfiz Markaz Hadits Bilal bin Rabah Aliyah Legok Islamic Boarding School, is located in the village of Cirarab, where many of the residents make their living as factory workers, freelance workers transporting sand and gravel, farmers and others. This Islamic boarding school is located on waqf land of approximately 800m2 with a mosque, classrooms, student and teacher dormitories as well as the principal's residence. The mosque is the main facility where students carry out worship and activities, it is also a place of worship for local residents and is also a place where studies or lectures are carried out by resource persons or teachers from various scientific backgrounds, both for students, the surrounding community and the supervisors and administrators of Islamic boarding school activities. To support these activities, a good audio sound system is needed to carry out the call to prayer as well as other announcements and other forms of activities. For this reason, indoor out loudspeakers with optimal power and the right direction and location are needed, the wider the area, the greater the power requirement. However, what needs to be paid attention to is the power distribution. It is better to place several speakers with smaller power spread out at certain points than large power speakers but only placed at one point and the right power amplifier is to use a Toa power amplifier. To optimize the indoor sound system of the mosque at the Tahfiz Markaz Hadits Bilal Bin Rabah Aliyah Legok Islamic Boarding School, the PKM Team for the Electrical Engineering Study Program at Pamulang University carried out a PKM entitled Training on Mosque Area Sound System Installation at the Tahfidz Markaz Hadits Bilal Bin Rabah Islamic Boarding School Cirarab Legok Tangerang Banten.